Wetting and low temperature bonding of zirconia metallized with Sn0.3Ag0.7Cu-Ti alloys. Issue 10 (July 2018) - Bian, H.; Fu, W.; Lei, Y.Z.; Song, X.G.; Liu, D.; Cao, J.; Feng, J.C.
Abstract: The wettability of zirconia with Sn0.3Ag0.7Cu-Ti (SAC-Ti) alloys was investigated via the sessile drop method with the increase of temperature. Zirconia, pre-metallized with SAC-Ti metal powder at 900 °C, was brazed to copper using an SAC solder paste at the low temperature of 250 °C. The active element Ti reduced the contact angle as the temperature increased. The lowest contact angle of 8° was obtained with SAC-4 wt% Ti which possessed sufficient Ti and appropriate fluidity. When zirconia was pre-metallized with SAC-4 wt% Ti alloy, the typical microstructure of the copper/SAC/zirconia joint was copper/Cu6 Sn5 layer/β-Sn layer containing Ti3 Sn and Ti6 Sn5 phases/Ti3 Sn layer/TiOx layer/zirconia. As the Ti content increased, more Ti-Sn intermetallic compounds remained in the seam, and the shear strength increased first and thereafter decreased. The highest shear strength of 19.1 MPa was achieved as zirconia was pre-metallized with SAC-4 wt% Ti. Fracture analyses indicated that brittle fracture was initiated at the reaction layers adjacent to zirconia and propagated in the seam during shear test.